O ensinar na ótica de professoras de uma rede municipal de ensino: desafios, práticas e o sentido da escola - Martins, Francine de Paulo (2014)
The aim of this research was to investigate, in the view of teachers from a municipal school system, how teaching is developed and what main challenges are faced by them in their teaching practice as well as what meaning they attribute to school. Procedures for data collection were used such as: focus groups involving 42 teachers; questionnaire for characterization of the teachers personal and professional profile; semi-structured interviews; data analysis of the 2012 School Census and official documents of the Municipal Department of Education. The research used theoretical contribution from Nóvoa (2009), Young (2011); Saviani (2012); Libâneo (2012), concerning school function. Roldão (2006; 2010); Nóvoa (1999; 2009) and Charlot (2000; 2005; 2008) for discussions on teaching and on mobilization for learning. The data analysis reveals that the strategies used for teaching are various and seek the student s mobilization for learning. The teachers evidence the complexity of teaching and learning processes, especially with regard to the effective mobilization of the student for learning. The belief in the student s ability, the concern with his/her learning conditions denote the responsibility of the teachers towards the educational process and student's school life. Despite the fact that the teachers signal that many are the challenges that they face and that they several times take over responsibilities which are beyond teaching, they show great commitment to their profession and satisfaction when they see that the student has learned and has been changed by teaching. They understand that the school is primarily responsible for teaching; however, they refer to the student s reception, responsible citizenship development and autonomy promotion as school s functions. We believe that by giving voice to teachers, we can capture the vision and thoughts of those who teach. Consequently, we approach the classroom, the contradictions and conflicts concerning the school and the student s daily life, as well as the teaching and learning process, and in particular the teachers , their beliefs and conceptions to understand and discuss teaching. This research brings us contributions for thinking teaching over in order to overcome the reductionist discourses on teaching, inspiring new perspectives and ways of considering school, the teacher and the teaching and learning process